Pengaruh Atribut Produk, Citra Merek, Harga Terhadap Keputusan Pembelian Sepeda Polygon Dalam Masa Pandemi Covid-19 - Mila Dia Nor Asiya; Winarto; Febrina Hambalah (Journal Of Accounting and Business, 2023)
Pandemic Covid-19 is an outbreak that creates new habits for people who start implementing health protocols starting from activities that also have a positive influence on the body. Cycling is one of the activities carried out by the community in their activities and spare time. Various bicycle brands are present in Indonesia, such as the Polygon Strattos S2, which is able to become a consumer choice in bicycle purchasing decisions. This study discusses the Influence of Product Attributes, Brand Image and Price on Polygon Bike Purchase Decisions during the Covid-19 Pandemic which focuses on the Strattos S2 type of bicycle which is a road bike. This research certainly has research respondents, namely the SCC (Strattos Cycling Club) bike community, totaling 45 respondents. The research technique used is non-probability sampling using questionnaires distributed to respondents. The data that has been obtained is processed using Staticial Product and Service Solution (SPSS) Software. After that, analysis was carried out using IBM SPSS Statistics 16. The results obtained showed that Product Attribute Variable (1) had a significant and positive effect on the Purchase Decision variable, Brand Image Variable (2) obtained significant and positive results on the Purchase Decision variable, Price Variable ( 3) shows that there is a significant and positive effect on the Purchase Decision variable.